2015
DOI: 10.1111/ijcs.12220
|View full text |Cite
|
Sign up to set email alerts
|

Who buys from farmers’ markets and farm shops: The case of Germany

Abstract: In this article, we analyze the influence of sociodemographic factors and consumer attitudes toward direct marketing products and sources (outlets) on the frequency of buying food from farmers’ markets and farm shops. By conducting an intercept survey with pedestrians in 2011 and 2012, we interviewed a total of n = 550 consumers. The target regions of the study were the Eastern German federal states. The study uses two ordered logit regression models to investigate consumers’ shopping behaviour at farmers’ mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
2
24
0
3
Order By: Relevance
“…Therefore, the study suggests that the integration of second‐home owners into the local community is a crucial pre‐condition for local food sales. It seems obvious that in Finland there is a group of second‐home owners who have strong ties to the place and who are committed to support local producers, which at the same time supports previous findings about consumer motivations behind direct purchases from farmer's markets (Bavorova, Unay‐Gailhard, & Lehberger, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the study suggests that the integration of second‐home owners into the local community is a crucial pre‐condition for local food sales. It seems obvious that in Finland there is a group of second‐home owners who have strong ties to the place and who are committed to support local producers, which at the same time supports previous findings about consumer motivations behind direct purchases from farmer's markets (Bavorova, Unay‐Gailhard, & Lehberger, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…No consensus exists on the definition of "local food". The key elements of existing definitions range from distance of food travel (from 10-31 miles to as high as 400 miles; Adams & Adams, 2011;Canadian Food Inspection Agency, 2019;Martinez et al, 2010), driving hours (e.g., within six to seven hours; Zepeda & Leviten-Reid, 2004), geographic boundaries (e.g., given states, regions, countries; Conner, Montri, Montir, & Hamm, 2009), regional specialties (Adams, 2018), and marketing distribution channels (e.g., farmers' markets, farm retailers; Bavorova, Unay-Gailhard, & Lehberger, 2016) to emotion-or relation-related foods (e.g., foods from one's hometown, neighbours, or relatives ;Feldmann & Hamm, 2015). Researchers have demonstrated that local food cannot be regarded as a definite entity and consumers perceive local food differently according to their spatial and social context (Carroll & Fahy, 2014).…”
Section: Local Foodmentioning
confidence: 99%
“…For example, when consumers recognize the benefits of locally produced products, such as that locally produced products are more environmentally friendly/healthier/tastier and have better quality, they are willing to pay a premium price for them (Denver & Jensen, 2014). Perceived freshness of local foods and the feeling of supporting local farmers have a positive relationship to consumers' local food purchase (Bavorova et al, 2016). Adams and Adams (2011) find that farmers' market shoppers are willing to pay a large price premium for local foods.…”
Section: Locavorismmentioning
confidence: 99%
“…This study employed ordered logit regressions to understand what factors were associated with preferences toward food quality. Ordered logit models are largely used in discrete choice analysis and are a useful tool to specify the probability of choosing one option among a set of alternatives (Bavorova, Unay‐Gailhard, & Lehberger, ; Thilmany, Bond, & Bond, ; Verbeke & Ward, ).…”
Section: Data Collection and Methodologymentioning
confidence: 99%